Rasio Likuiditas, Manajemen Asset, Manajemen Utang, Aktivitas untuk Mengukur Kinerja Keungan Perusahaan Pertambangan di Bursa Efek Indonesia - Yun Milly Basa Turnip; Deasy Arisandy Aruan; Helda Sefty Christiani Br Pinem; Agnes Monica Angel Situmorang (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the partial impact of liquidity ratios, asset management, debt management, and activities on the financial performance of mining sub-sector companies listed on the IDX for the period 2017-2019. This research method is descriptive quantitative. Study data obtained is an annual report contained in the IDX. There are 47 companies listed on the IDX as the population used by the authors in this study. The results showed, a) the CR variable has a value of t count < t table that is -0.534 < - 2.00172 with a significant value of 0.596 > 0.05; b) TATO variable has a value of t count < t table that is 0.482 < 2.0172 with a significant value of 0.000 < 0.05; c) the DAR variable has a value of t count < t table, namely -1.635 < - 2.0172 with a significant value of 0.107 > 0.05; d) the FATO variable has a value of t count < t table that is 1.755 < 2.0172 with a significant value of 0.085 > 0.05. All independent variables affect the dependent variable which can be seen from the determination coefficient test of 46.4% of financial performance which can be clarified by four independent variables. In conclusion, financial performance is significantly influenced by liquidity ratios, asset management, debt management, and activities. Keywords: Activities, Financial Performance, Asset Management, Debt Management, Liquidity Ratio